2004
DOI: 10.1103/physrevd.70.124005
|View full text |Cite
|
Sign up to set email alerts
|

Time scale for loss of massive vector hair by a black hole and its consequences for proton decay

Abstract: It has long been known that matter charged under a broken U(1) gauge symmetry collapsing to form a black hole will radiate away the associated external (massive) gauge field. We show that the timescale for the radiation of the monopole component of the field will be on the order of the inverse Compton wavelength of the gauge boson (assuming natural units). Since the Compton wavelength for a massive gauge boson is directly related to the scale of symmetry breaking, the timescale for a black hole to lose its gau… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…The author of this paper concluded that the monopole massive vector field created by spherically symmetric distribution of charged matter collapsing into a Schwarzschild BH does have the decay time scale governed by the Compton wavelength of the corresponding gauge boson. Thus, according to the results of [12], the prediction of [11] is correct at least in the monopole case.…”
Section: Introductionmentioning
confidence: 72%
See 3 more Smart Citations
“…The author of this paper concluded that the monopole massive vector field created by spherically symmetric distribution of charged matter collapsing into a Schwarzschild BH does have the decay time scale governed by the Compton wavelength of the corresponding gauge boson. Thus, according to the results of [12], the prediction of [11] is correct at least in the monopole case.…”
Section: Introductionmentioning
confidence: 72%
“…In this paper we show that the time scale of the screening and the Proca hair loss is equal in order of magnitude to the gravitational radius of the BH and, therefore, the result of [12] is incorrect. We analytically calculate the evolution of the field of the uniformly charged spherical shell surrounding the BH and contracting according to some undefined law.…”
Section: Introductionmentioning
confidence: 86%
See 2 more Smart Citations
“…Possibility of violation of the EEP near a black hole could be suggested by the superradiance process of rotating black holes [62][63][64][65][66], which implies there might be a fruitful environment of light particles around rotating black holes at horizon scale [67][68][69][70][71][72][73]. Moreover, if these particles are those beyond the standard model and are coupled to photons, there might be a phenomenological violation of EEP.…”
Section: Introductionmentioning
confidence: 99%